2002
DOI: 10.1677/joe.0.1740455
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral but not central leptin prevents the immunosuppression associated with hypoleptinemia in rats

Abstract: Leptin is a peripheral immunoenhancing reagent that directly activates splenic lymphocytes in mice. We found that a 48 h fast in rats resulted in a decrease in serum leptin that was accompanied by a lower delayed-type hypersensitivity (DTH) response. Peripheral leptin replacement completely restored this response in fasted animals. We employed a recombinant adeno-associated virus (rAAV) system to deliver leptin gene directly into rat brain to assess the effect of sustained long-term central expression of lepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
0
8
0
1
Order By: Relevance
“…Similarly, humans with congenital leptin deficiency have a much higher incidence of infection-related death during childhood (Ozata et al, 1999), whereas recombinant human leptin (rmetHuLeptin) administration in two children with congenital leptin deficiency normalized absolute numbers of naive CD4 + CD45RA + T cells and nearly restored the proliferation response and the cytokine release profile from their lymphocytes (Farooqi et al, 2002). A number of studies in mice have shown that the effect of leptin on the immune system is both direct and indirect, i.e., via modulation of central or peripheral pathways (Fraser et al, 1999;Zhang et al, 2002).…”
Section: Leptin In Innate and Adaptive Immune Responsementioning
confidence: 99%
“…Similarly, humans with congenital leptin deficiency have a much higher incidence of infection-related death during childhood (Ozata et al, 1999), whereas recombinant human leptin (rmetHuLeptin) administration in two children with congenital leptin deficiency normalized absolute numbers of naive CD4 + CD45RA + T cells and nearly restored the proliferation response and the cytokine release profile from their lymphocytes (Farooqi et al, 2002). A number of studies in mice have shown that the effect of leptin on the immune system is both direct and indirect, i.e., via modulation of central or peripheral pathways (Fraser et al, 1999;Zhang et al, 2002).…”
Section: Leptin In Innate and Adaptive Immune Responsementioning
confidence: 99%
“…A number of studies in mice have shown that the effect of leptin on the immune system is both direct and indirect, i.e., via modulation of central or peripheral pathways (28,29).…”
Section: Cd45ramentioning
confidence: 99%
“…For example, a single intracerebroventricular (i.c.v) injection of constitutively active rAAV-leptin was recently shown to impair T-lymphocyte-mediated immunity in rats. 22 As discussed previously, leptin overexpression could also have negative effects on the reproductive system 10 and skeletal system. 11 Should such sideeffects appear, transgene expression could be reduced or silenced if the gene delivery system incorporates regulation.…”
Section: Discussionmentioning
confidence: 91%